2021
DOI: 10.3390/ijerph18189645
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Potential Benefits of Accumulated Multicomponent-Training in Non-Active Older Adults: From Physical Fitness to Mental Health

Abstract: The present study aimed to analyze the impact of a multicomponent training (MCT) program in a group of non-active older adults, comparing two different dose distributions. Twenty-four individuals, assigned to two groups, completed 15 weeks of MCT (2 days/week). The continuous group (CMCT; n = 14, 9 females; 71.07 ± 5.09 years) trained for 60 min/session in the morning. The accumulated group (AMCT; n = 10, 5 females; 72.70 ± 3.59 years) performed the same exercises, volume, and intensity, but the training was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
(129 reference statements)
1
2
0
Order By: Relevance
“…The METP resulted in the improvement of the study of health profiles of older women, similar to a study by Douda et al [ 28 ] that reported increases in muscular strength, cardiorespiratory capacity and flexibility after periods of nine months of METP over five years and in the same direction as Monteagudo et al [ 29 ] and Bezerra et al [ 30 ]. Sobrinho et al [ 20 ] showed only 14 weeks of an METP combined with flexibility training is enough to promote increases in the flexibility of inactive older women and improvements in blood pressure.…”
Section: Discussionsupporting
confidence: 79%
“…The METP resulted in the improvement of the study of health profiles of older women, similar to a study by Douda et al [ 28 ] that reported increases in muscular strength, cardiorespiratory capacity and flexibility after periods of nine months of METP over five years and in the same direction as Monteagudo et al [ 29 ] and Bezerra et al [ 30 ]. Sobrinho et al [ 20 ] showed only 14 weeks of an METP combined with flexibility training is enough to promote increases in the flexibility of inactive older women and improvements in blood pressure.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, participation in multimodal exercise is an important strategy for maintaining mental health in older adults. 24 , 25 A 24-month intervention with a 2-year follow-up showed that multi-component exercise improved the physical and psychological dimensions of quality of life in older adults with diabetes. 26 Similarly, a 12-week multimodal exercise intervention was found to be effective in improving quality of life in older adults with balance disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, parts of them were conducted with a single-group study design [ 19 , 20 , 24 ], and diverse outcome measures and various program contents used among these studies made consistent results difficult [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Another, according to the American College of Sports Medicine (ACSM) and systematic review recommendations, the multicomponent programs involving diverse physical capacities, such as flexibility, strengthening, balance and endurance, are more effective for the physical performance and healthy status of the community older adults [ 28 , 29 , 30 ]. From a practical, public health, cost-effectiveness and long-lasting perspective under the government-promoted health program, it could be valuable and critical to design an exercise protocol including domains of flexibility, strength and balance by using a package of low-cost and accessible exercise tools for the community older adults participating in CCS services, and investigate its effects on physical mobility and function.…”
Section: Introductionmentioning
confidence: 99%